Performance Evaluation of QUIC Protocol in Message Replication Overhead in PBFT Consensus using NS-3 - Habibi, Thio Lutfi; Sari, Riri Fitri (International Journal of Electrical, Computer, and Biomedical Engineering, 2023)
The development of protocols in the ICT world to increase reliability and speed in data traffic gave an inspiration to a new protocol called the QUIC protocol. The QUIC protocol is expected to improve the performance of Transport Control Protocol (TCP). In addition, developments also occur in blockchain technology where the protocol used in this technology still uses the existing TCP protocol. In this paper, we aimed to research whether the QUIC protocol implementation in blockchain infrastructure could improve the performance of the blockchain infrastructure itself, in terms of the time required for transactions. We focus on conducting research to measure the overhead time reduction of Practical Byzantine Fault Tolerance (PBFT) consensus by implementing the QUIC protocol, the consensus propagation process is a crucial phase in Blockchain. For simulation we used NS-3 discrete simulation environment to conduct scenario and our simulation result showed that the QUIC Protocol have potential significant performance compared to TCP Protocol in large datasets, on the other hand QUIC protocols have more room for improvement by implementing appropriate congestion algorithms.